Effect of 12 weeks Aerobic Exercise on Osteocalcin and Bone Density Indices in Overweight Women - Vahideh Zalouli, Hosnieh Rajavand, Asghar Tofighi (Pakistan Journal of Medical & Health Sciences, 2022)
Obesity is one of the major and most common metabolic disorders in all countries of the world, especially industrialized countries. Obesity has many consequences and complications, including metabolic diseases such as diabetes, metabolic syndrome and cardiovascular disease. The aim of this study was to evaluate the biochemical parameters such as vaspin, insulin and blood glucose in the blood of overweight women aged 35 to 45 years. Materials: In this study, 20 overweight women aged 35 to 40 years who They were divided into two separate experimental and experimental groups. After 12 weeks of continuous aerobic exercise, The mentioned indicators were measured. Results: In this study, it was found that there is a significant relationship between aerobic exercise and the amount of biochemical indicators of the body and the amount of body mass index of these women. Conclusion: According to the results of this study, it can be concluded that having a proper nutritional pattern along with proper exercise, including aerobic exercise, can play a very important role in reducing diseases such as obesity. And have subsequent effects.